The psychosocial challenges of mothers of children with thalassemia: A qualitative study - Majedeh Nabavian; Fatemeh Cheraghi; Farshid Shamsaei; Lily Tapak; Ahmad Tamaddoni (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Caring for the children suffering from thalassemia is a stressful experience with various aspects making the mothers face various challenges. Thus, the present study aimed to explain the psychosocial challenges of mothers with thalassemia children based on their lived experience. MATERIALS AND METHODS: In this qualitative study, which was conducted using the phenomenological method, 14 mothers with thalassemia children were selected from two thalassemia treatment centers in Hamadan and Babol (Iran) in 2020 using the purposive sampling method. Data were collected using in-depth and semi-structured interviews and were analyzed by van Manen's phenomenological methodology. RESULTS: In the first stage of data analysis, 534 initial codes were extracted, which were reduced to 290 by comparison and integration. The primary themes turned into 24 secondary themes after clustering. By comparing the secondary themes, three main themes (i.e., "psychological distress," "bodily burnout," and "mothers' need to empathy and support") with 7 secondary themes (i.e., "emotional exhaustion," "mental strain," "social stigma," "acute psychosomatic reactions," "long-term psychosomatic consequences," "expectation of family support," and support needs outside the family) were extracted. CONCLUSION: The results indicated that mothers with thalassemia children experience several challenges in various aspects. Therefore, they require care interventions and psychosocial support.